1993
DOI: 10.1111/j.1600-0447.1993.tb03454.x
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical eating disorders in male athletes

Abstract: This study investigated the possibility that male athletes who, owing to the rules of their sport, are pressured to maintain a low weight show an elevated prevalence of subclinical eating disorders. Twenty-five wrestlers and 59 rowers in the lower weight categories were investigated using the Eating Disorder Inventory (EDI). Fifty-two percent of the athletes reported the occurrence of binging. The EDI profiles of 11% of the athletes suggested the presence of a subclinical eating disorder. These figures are cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 36 publications
0
25
0
2
Order By: Relevance
“…2 6 College athletes are particularly susceptible to the dangers of developing eating disorders. [7][8][9][10][11] Skolnick 10 reported "seriously abnormal eating patterns" in 15.4% of female college swimmers and 62% of college gymnasts. Thiel et al 11 reported that 11% of male rowers and wrestlers in their study displayed eating disorders, and 52% of this population engaged in bingeing as a method of weight control.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 6 College athletes are particularly susceptible to the dangers of developing eating disorders. [7][8][9][10][11] Skolnick 10 reported "seriously abnormal eating patterns" in 15.4% of female college swimmers and 62% of college gymnasts. Thiel et al 11 reported that 11% of male rowers and wrestlers in their study displayed eating disorders, and 52% of this population engaged in bingeing as a method of weight control.…”
mentioning
confidence: 99%
“…Thiel et al 11 reported that 11% of male rowers and wrestlers in their study displayed eating disorders, and 52% of this population engaged in bingeing as a method of weight control. Similarly, DePalma et al 12 reported that 9.9% of lightweight football players were at risk for eating disorders, and fully 42% practiced dysfunctional eating behaviour to meet the weight restrictions of their sport.…”
mentioning
confidence: 99%
“…By cutting to a lower weight class, wrestlers reportedly gain an advantage against a smaller opponent. Athletes referred that prolonged fasting and fluid restriction are followed by binge eating (Steen & Brownell, 1990;Thiel, Gottfried, Hesse, 1993). Andersen and coworkers (1995) found that many competitive body builders experience b s of control over eating after competition.…”
mentioning
confidence: 97%
“…Anorexia has been the third most chronic condition for teenage girls (Treasure & Kordy, 1998) and traditionally, gender has been considered one of the most important predictors of the risk for developing an ED (Striegel-Moore & Bulik, 2007;Touchette et al, 2011). Epidemiological data about the prevalence and characteristics of ED in males are lacking, but there are reports about the increasing risk of ED in males (Herzog, Norman, Gordon, & Pepose, 1984;King, 1990;Pope, Katz, & Hudson, 1993;Striegel-Moore, Silberstein & Rodin, 1986;Thiel, Gottfried, & Hesse, 1993). Early diagnosis of ED improves the prognosis, but individuals with disordered eating frequently do not seek professional help in time (Shader, 1994).…”
Section: Introductionmentioning
confidence: 99%